The Lecturer Perception on the Aplication of Learning Management System (LMS) in the Teaching E-Learning Proccess in Lecturers English Department - Inda Indrawati (Jurnal Multidisiplin Madani, 2022)
The objective of the research is to determine Lecturer Perception on Using LMS in  Teaching E-Learning Process in Teacher English Department. It was aqualitative research used 3 lecturers and 4 students as a sample. They were the lecturers of English Department in academic years 2020/2021. The data analysis technique is descriptive qualitative.The results of this study indicate that as long as lecturers use LMS are  (a) in perceive e ase of use it is found score of lecturers are 4,7% strongly agreed and agreed 52,3% and doubted is 42,80%. (b) in  perception of the usefulnessis strongly agreed 17% and agreed 56% although doubted is 27,70%.(c) attitude toward the use of LMs is strongly agreed 22%, agreed 44% and doubted is 33,30%. (d) behavioral intention to use, score is agreed 83% and doubted 66,65 (e) job  relevance, it is found that mean score of lecturer is agreed 67% and doubted 49,95%. Based on the results of the study, it can be concluded that the perception of English lecturers regarding the use of LMS is a positive idea. Based on interview of students perception of English department in six semester those are MN, AAF, SN, and MA of using LMS in teaching learning process that the researcher conclude those students are easy to access LMS, Students perception based on the important of using LMS is very useful for this time.